A survey on the energy consumption and demand in a school (2010)
Efforts to reduce energy consumption in domestic buildings and commercial areas have been intensified recently in view of the limiting of the growing demand for electricity and the efforts to reduce CO2 Investigations into energy reduction strategies have been extensive with active and rigorous researches carried out successfully in many countries of the world. A walk-through energy audit was conducted in the School to determine the peak energy demand of the entire School as well as flagged areas for possible energy savings. For the purpose of this study, the School is broken down into about thirty four offices. This paper presents a walk-through energy audit of a School located in Ibadan, Nigeria. A total of about 40.4 kWh of electrical energy per day is required by the School for running all the electrical and mechanical appliances. To reduce the strain on the school's electrical supply systems and hence prevent system outages, the following peak demand reducing strategies have been recommended: Load reducing strategies, High efficiency equipment, Efficient lighting, Efficient air conditioning, Efficient refrigeration, Energy source substitution and on-site heat and electricity generation. It was recommended that this energy audit manual should be used as guide anytime any energy consuming machine is to be installed in the School.